Factors affecting population dynamic and preference of Acyrthosiphon pisum Harris in winter pea lines - Ivelina Nikolova (Journal of BioScience and Biotechnology, 2019)
Population dynamics and preference of Acyrthosiphon pisum Harris on six winter pea lines in field conditions were studied. Aphid number was recorded on marked plants by counting. The impact of several factors on the population growth and pea aphid choice during the period 2016–2018 was tracked. Weather condition strongly affected on the population dynamics of the pea aphid. The highest positive and significant effect on pea aphid infestation had the temperature (r = 6.748) followed by humidity (r =1.992). It was found that a peak in the aphid population density was reached in the sensitive stage of pod formation, as well as at flowering under a favorable weather condition. Among winter pea lines, lines 6 and 12A stood out with a significantly lower aphid density, nitrogen concentration and shorter generative period. They were much less preferred by aphids and defined as tolerant. Also, the interaction between aphid density and generative period as well as total nitrogen was positive and significant.